This book is for you : I hope you find it mildly uplifting - Worry Lines (Ten Speed Press, 2021)
"Worry Lines has captured hearts around the world with sweetly funny, deceptively simple, and instantly relatable daily drawings in Instagram. [This book] is a collection of fan-favorites interwoven with a new, fully illustrated story about hope, worry, and chocolate chip cookies."--Back cover.